Analysis of the Climate Signal in Subannual Width Measurements of Pinus nigra Tree Rings in Kastamonu Province, Turkey - Majeed, Mehvish; Stoica, Emanuel; Meko, David M.; Touchan, Ramzi; Sivrikaya, Fatih; Alexandru, Alin Madalin; Casanovas Arimon, Laia; Kvaratskhelia, Revaz; Maglakelidze, Sophio; Pacaldo, Joren Mundane; Deeksha (Tree-Ring Society, 2023)
Black pine (Pinus nigra) is a widely distributed tree species across southern Europe and Asia Minor. This article summarizes a dendroclimatological study of subannual P. nigra ring width conducted during an international summer course "Tree Rings, Climate, Natural Resources, and Human Interaction" in 2022. Increment cores were collected from 15 young (oldest 105 years) P. nigra trees in the Arac Forest District inKastamonu Province, Turkey. Site chronologies of earlywood (EW) and latewood (LW) width were developed to investigate climatic signals using correlation analysis. Results show thatEWand LW chronologies are significantly correlated with one another (r = 0.56, n = 105, p < 0.001) and positively correlated with precipitation in the months April-September of the growth year. The month of strongest correlation shifts from April for EW to July for LW. Analysis of seasonally aggregated climate data further shows that EW but not LW responds positively to precipitation in the preceding summer (July-September). These results suggest that future tree-ring studies aimed at tree-growth impact of climate change in the Black Sea region of Turkey exploit the climate signal in subannual ring widths of P. nigra.
Keywords: 13. Climate action; 15. Life on land